KONSEP ALIRAN FILSAFAT UTAMA PENDIDIKAN (PERENIALISME, ESENSIALISME, PROGRESIVISME, DAN REKONSTRUKSIONISME) DALAM PENDIDIKAN - Muhammad Latif Nawawi; Asmuni Asmuni; Hesti Winingsih; Moh Fuadi; Kasinyo Harto; Mardiah Astuti (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This journal discusses the concepts and implications of the four main currents in educational philosophy: Perennialism, Essentialism, Progressivism, and Reconstructionism. Each stream has a different philosophical foundation that shapes their views on purposes, teaching methods, as well as the role of teachers and students in the context of education. The perennial approach emphasizes universal values and the eternity of knowledge. The focus is on the core material that is considered to be the most important knowledge to be taught to students. Meanwhile, essentialism emphasizes the essential core of knowledge and skills that need to be learned so that students have a strong foundation in education. Progressivism offers a different perspective, emphasizing on experience, experimentation, and individual growth. This stream believes that students must engage in meaningful and relevant learning to the real world in order to develop critical thinking and creativity. Meanwhile, reconstructionism highlights the importance of education as a tool for changing societies. The focus is on questioning and reforming existing social structures and educational systems to better change. In this journal, an in-depth analysis is given of the perspective of each stream, as well as its practical application in the current educational system. Emphasis is placed on the role of teachers, learning strategies, and educational evaluation that corresponds to the philosophy of the respective stream. In conclusion, a comprehensive understanding of these major currents is essential for policymakers, educators, and educational practitioners to build a better framework in designing educational systems that respond to the needs and developments of modern societies.